Recurring patterns among scrambled genes in the encrypted genome of the ciliate Oxytricha trifallax. (7th December 2016) - Burns, Jonathan; Kukushkin, Denys; Chen, Xiao; Landweber, Laura F.; Saito, Masahico; Jonoska, Nataša
Abstract: Some genera of ciliates, such as Oxytricha and Stylonychia, undergo massive genome reorganization during development and provide model organisms to study DNA rearrangement. A common feature of these ciliates is the presence of two types of nuclei: a germline micronucleus and a transcriptionally-active somatic macronucleus containing over 16, 000 gene sized "nano-chromosomes". During conjugation the old parental macronucleus disintegrates and a new macronucleus forms from a copy of the zygotic micronucleus. During this process, macronuclear chromosomes assemble through DNA processing events that delete 90–98% of the DNA content of the micronucleus. This includes the deletion of noncoding DNA segments that interrupt precursor DNA regions in the micronucleus, as well as transposons and other germline-limited DNA. Each macronuclear locus may be present in the micronucleus as several nonconsecutive, permuted, and/or inverted DNA segments. Here we investigate the genome-wide range of scrambled gene architectures that describe all precursor-product relationships in Oxytricha trifallax, the first completely sequenced scrambled genome. We find that five general, recurrent patterns in the sets of scrambled micronuclear precursor pieces can describe over 80% of Oxytricha 's scrambled genes. These include instances of translocations and inversions, and other specific patterns characterized by alternating stretches of consecutive odd and even DNA segments. Moreover, we find that iterating patterns of alternating odd–even segments up to four times can describe over 96% of the scrambled precursor loci. Recurrence of these highly structured genetic architectures within scrambled genes presumably reflects recurrent evolutionary events that gave rise to over 3000 of scrambled loci in the germline genome. Abstract : Highlights: Five patterns describe over 80% of Oxytricha's completely annotated scrambled genes. A rearrangement pattern can have up to four equivalent representations. Inversions, translocations, and alternating odd–even patterns are most frequent. Nested instances of the five patterns account for over 96% of all scrambled genes.